Selection of doubled haploid black rice lines in advanced yield trial based on multivariate analysis (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Karima AW, Putri RK, Purwoko BS, Dewi IS, Suwarno WB, Kurniawati A. 2021. Selection of doubled haploid black rice lines in advanced yield trial based on multivariate analysis. Biodiversitas 22: 5425- 5431. Research on the development of black rice has not received much attention. The anther culture technique can shorten the plant breeding process and produce doubled haploid (DH) lines. The target of this study was to evaluate DH black rice lines with early maturity, good agronomic performance, and high yields. Twenty-seven doubled haploid lines and three check varieties (Aek Sibundong, Inpari 24, and Jeliteng) were evaluated at two locations (Kediri, East Java, and Bogor, West Java) from January to July 2020. A randomized complete block design was applied to this study with three replicates. The combined analysis results showed that the genotype effect (G) was highly significant (p < 0.01) for all characters. In addition, all characters had a high broad-sense heritability. Characters that were positively correlated with yield based on genotypic and phenotypic correlation were the number of productive tillers, the number of vegetative tillers, panicle length, the number of filled grains, and the number of total grains. The 1000-grains weight and panicle length had a positive and the largest direct effect on yield. Principal component analysis showed that the number of productive tillers and the 1000-grains weight were related to yield. The selection index model that can be formulated is as follows I = (3*0.375*Yield) + (0.723* 1000-grains weight) + (0.280* Number of productive tillers). Based on the selection index, 14 genotypes were selected.